Pendampingan Penggunaan Teknologi Secara Bijak Kepada Anak Sekolah Dasar di Pesisir - Nahdatul Khairunisa; Martin Kustati; Gusmirawati Gusmirawati (Jurnal Pemberdayaan Masyarakat, 2023)
Gadget is a technology that has a function to facilitate communication for humans. The advancement of gadget technology for the world of education also has a negative impact, which can cause students to be lazy to learn and play gadgets more often not on time. One of the activities is "Assistance in the Use of Technology Wisely to Elementary School Children on the Coast" considering the low knowledge of students about the functions and benefits as well as the positive and negative impacts of using gadgets. This activity aims to provide an understanding of the functions and benefits and impacts of using gadgets and motivate students to be wiser in using gadgets. This method of implementation is the PAR (Participary Action Research) methodology is an approach whose process aims at learning in overcoming problems and meeting the practical needs of the community, as well as the production of science. The results of this activity are expected impact on students can apply the use of gadget technology wisely as needed so as not to harm themselves and others.